Phase II Clinical Trial to Establish Efficacy of a Locally Appropriate Bivalent Anti Snake Venom in Pakistan - Quraishi, Naeem; Ahmad, Tasneem; Ghanghro, Allah-Bux; Arejo, Abdullah; Muhammad, Sharib S.; Chandio, Atta (Journal of Pharmacy and Nutrition Sciences, 2017)
Objective: This study was conducted to determine the efficacy of Snake anti-venom Immunoglobulin [IgG] manufactured by Anti-Snake Venom [ASV]/Anti-Rabies [ARV] Serology Laboratory, Health Department, Government of Sindh. Methods: The prospective, observational single arm study was conducted after the approval of IRB. Study included six patients with viper [Echis carinatus sochureki] snakebites referred to the emergency ward of Peoples University of Medical & Health Sciences Hospital, Nawabshah and District Headquarter Hospital Mithi, Sindh, Pakistan with consultation of Clinical and Principal investigator. The study was conducted over a period of three months [August 2015 to November 2015]. All patients were given IV infusion of 10 mL [1 vial] investigational ASV diluted in 100 mL normal saline except one patient who received 5 mL management dose and 5 mL subsequent dose for the recovery of coagulopathy. The efficacy was assessed by Primary and secondary efficacy endpoints, i.e. the dose at which maximum no of patients were treated [permanent restoration of normal blood coagulation tested by 20-minute whole blood clotting test [20-minute WBCT] with minimum toxicity. Results: All patients recovered from coagulopathy after receiving IV infusion of 10 mL investigational ASV diluted in 100 mL normal saline tested by 20-minute WBCT. Mean Recovery time was 9:15 ± 3:25 hours. Conclusion: Safety and efficacy was assessed for the Bivalent Anti venom Immunoglobulin-NQ1 [IgG] manufactured by ASV/ARV Serology Laboratory, Health Department, Government of Sindh.